GENETIC ANALYSIS OF TRANSGRESSIVE SEGREGATION IN BACKCROSS DERIVED INTROGRESSION POPULATION OF ORYZA SATIVA CV. SAMBA MAHSURI / O. RUFIPOGON FOR YIELD ENHANCING TRAITS - and R. JAGADEESHWAR, P. S. BASAVARAJ, C. GIREESH, CH. DAMODAR RAJU, M. SHESHU MADHAV (The Journal of Research, PJTSAU, 2020)
Rice (Oryza sativa L.) is a major cereal food crop and consumed by nearly half of the world’s population. It constitutes for 35 - 75% of caloric uptake by Asians and planted over 11% of global arable land (Khush, 2005). Because of its agricultural importance, rice has been bred intensively resulting in the doubling of the production by adopting high-yielding varieties/ hybrids. However, this achievement has led to the narrowing of the available genetic base in elite germplasm and is causing much concern about the reduced genetic gain in present day rice breeding. In a genetic diversity study, Sun et al., (2001) reported that cultivated rice has only 60% of the alleles of wild rice. A large amount of genetic variation in the genus Oryza lies unexploited in wild progenitors (Wang et al., 1992). Hence, attention is being shifted to map yield-enhancing QTLs and enrich the cultivated gene pool by introgression of favorable genes/gene complexes from wild species (Tanksley and McCouch, 1997; Swamy and Sarla, 2008). The potential of wild relatives to increase the genetic variability in cultivated rice is becoming increasingly obvious (Vaughan, 1994). The increased variability occurs both by introduction of the pre-existing alleles of wild species and also a lot of genetic variability is created de novo (Wang et al., 2005; Wang et al., 2010).